Intranasal fluticasone associated with delayed tympanostomy tube placement in children with eustachian tube dysfunction. (March 2017) - Crowson, Matthew G.; Ryan, Marisa A.; Ramprasad, Vaibhav H.; Choi, Kevin J.; Raynor, Eileen
Abstract: Objectives: Pediatric patient caregivers may prefer to avoid a surgical intervention and request a medical management option for eustachian tube dysfunction (ETD). However, there are limited published data evaluating the efficacy of intranasal fluticasone in the medical management of ETD as an alternative to tympanostomy tube placement. The objectives of this study were to: 1) determine if intranasal fluticasone (INF) prevented tympanostomy tube placement in children with ETD, and 2) describe differences in patient response to INF related to cleft lip and/or palate (CLP) and Down syndrome. Methods: Case series with planned chart review at a Tertiary academic hospital. We reviewed pediatric patients treated with INF for ETD. Inclusion criteria included ETD, no prior intranasal or oral steroid therapy, and no prior tympanostomy tube placement. Outcomes included time-to- tympanostomy tube placement with or without INF and therapy compliance. Kaplan-Meier survival analyses with log-rank tests and Fisher's exact tests were used to examine outcome variables. Results: 676 fulfilled inclusion criteria. 393 (58.7%) were male, and 355 (52.5%) Caucasian with mean age of 27.1 months old. 92 (13.6%) had CLP and 46 (6.8%) had Down Syndrome. 266 (39.4%) received INF, and 202 (88.2%) were compliant at their next visit. 474 (70.1%) had tympanostomy tubes placed. Children treated with INF were less likely to have tympanostomy tubes placed than children not treated (52.6% vs. 81.5%; p < 0.0001). Using survival analyses, INF use was associated with significantly longer mean time-to-tympanostomy tube than no INF use (199.4 vs. 133.7 days; p < 0.0001). INF did not reduce time-to-tympanostomy tube in patients with CLP (p = 0.05) or Down Syndrome (p = 0.27). Conclusion: INF significantly reduces the number of children requiring tympanostomy tube placement for ETD. The CLP and Down Syndrome anatomical variants may attenuate INF efficacy. Further in vivo characterization of INF action on eustachian tube tissues will help further substantiate these observations.